SISTEM INFORMASI PERPUSTAKAAN DI SMP NEGERI 12 KOTABUMI BERBASIS BORLAND DELPHI 7 - Jihad Plaza R, M. Abu (Jurnal Informatika, 2015)
Libraries play an important role in advancing the institute of education because the library is a place to improve knowledge for the students. In the library of SMPN 12 Kotabumi running processes such as borrowing books, returning books, encode books, the data replace data of members and replace of data administration are still modest. Avoid delays in the system library services SMPN 12 Kotabumi, it is necessary to design an application system library that can help and easier the activities of the circulation of the book. In designing the application system library of SMP N 12 Kotabumi uses prototype method and Unified Modeling Language (UML) as well as for language programmer using the Borland Delphi 7, with a SQL Server database. Application system design library of SMP N 12 Kotabumi is used to support library activities such as record and data processing of member, the data of book, the data borrowed, the data returns, late charges and catalog book.Hopefully with this library application system design it can solve the problems which exist in the library and can help in the development of science students.Key Words : Borland Delphi 7, Libraries, Prototype, Unified Modeling Language (UML).